The Influence of Remuneration, Work Ethic and Organizational Culture on Improving Human Resource Culture at the Ministry of Religion Office of South Tangerang City - Sarwani Sarwani (Universitas Dharma Wacana, 2022)
This study aims to determine the effect of remuneration, work ethic, organizational culture and corporate image on improving the quality of Human Resources at the Office of the Ministry of Religion, South Tangerang. The method used is quantitative, the sampling technique uses saturated sampling totaling 140 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Remuneration research results have a positive and significant effect on improving the quality of human resources, this is indicated by the value of t count > t table or (7.254 > 1.977) this is strengthened by a significance of 0.000 <0.05. Work ethic has a positive and significant effect on improving the quality of human resources, this is indicated by the value of t count > t table or (8.857 > 1.977) this is strengthened by a significance of 0.000 <0.05. Organizational culture has a positive and significant effect on improving the quality of human resources, this is indicated by the value of t count > t table or (8,155 > 1.977) this is reinforced by a significance of 0.000 <0.05. Remuneration, work ethic and organizational culture simultaneously have a positive and significant effect on quality improvement, this is indicated by the calculated F value > F table (47.619 > 2.670) and sig. < 0.05 (0.000 < 0.05) with an influence contribution of 51.2%.Â